PENGARUH KONDISI PENCAHAYAAN TERHADAP HASIL SURVEI KECEPATAN KENDARAAN DENGAN PORTABLE SPEED GUN DAN APLIKASI BERBASIS ANDROID - Udi Subagyo Udi Subagyo; Achendri .Kurniawan (Jurnal Qua Teknika, 2021)
Technological advances developed rapidly with the use of the Android system in 2007. Android is an operating system or mobile-based operating system that is very widely used today. Mainly on smart phones (smartphones) or tablets. In addition, Android has a large community of application developers that extend the functionality of the device, generally written in a customized version of the programming language. One of the applications based on android is the "Speed ​​Gun" application. This application functions to measure the speed of an object moving by touch such as a velocimeter. The expected objective of the results of this study is to determine the results and the difference between the vehicle speed survey method using a portable speed gun and Android-based applications in each period. And the effect of lighting between the morning and evening periods on portable speed gun equipment and Android-based applications for vehicle speed surveys.The results of the speed survey using the speedgun android application equipment show that the speed data is close to the manual method, the difference in speed using the portable speedgun equipment for the afternoon period has an average difference of 9.2 km / hour which is the biggest difference compared to the speed difference between the speedgun android application equipment. and the manual method and the use of equipment for lighting conditions, shows that the portable speedgun equipment is highly influenced by lighting conditions, where from the analysis of the morning period, the average difference is 2.3 km / hour and the average difference is 9.2 km / evening.